SWOT ANALYSIS IMPLEMENTATION’S SIGNIFICANCE ON STRATEGY PLANNING - Omer, Soran Kakarash (Journal of process management and new technologies, 2019)
The important aim of this research is to evaluate the role of SWOT analysis on strategy planning that was used by the Samsung mobile company. As well SWOT Analysis is an independent variable and strategy planning is a dependent variable. This project has divided in to two basic parts theoretical and analytical. The theoretical part was focused on the theoretical knowledge relevant to the analysis of market strategy planning. The practical describes the current marketing strategy of the Samsung mobile company. Furthermore, the ways are depending on the number of issues by reviewing books and journals, also tracking down the information of the Samsung Company as a Global brand. The consequences show that accurate information which can be got managers through the analyses of the SWOT, marketing mix and the company strategy planning, the common conclusion is that SWOT analysis has the importance impacts on making strategic plan for a long time. This research has determined a very positive recommendation Samsung sustains remarkable investigation, enterprise and industrial or electronic competences however, it occurs to have disappear it is edge or level in advertising. This organization may require renovating its smartphone marketing and maybe restructure or redesign efforts and in order to maintain sharing or market portion critical grounds compare to country such as U.S. Innovative experiences for example, Samsung Remuneration will be somber if this company wants to conserve its position as a manufacturing leader. Samsung will also need to learn to deal with destructive Chinese opponents and Apple’s standing in terms of progresses.